Risk Factors, Clinical Outcomes, and Prognostic Factors of Bacterial Keratitis: The Nottingham Infectious Keratitis Study - Ting, Darren Shu Jeng; Cairns, Jessica; Gopal, Bhavesh P.; Ho, Charlotte Shan; Krstic, Lazar; Elsahn, Ahmad; Lister, Michelle; Said, Dalia G.; Dua, Harminder S. (Frontiers in Medicine, 2021)
Background/Aim: To examine the risk factors, clinical characteristics, outcomes, and prognostic factors of bacterial keratitis (BK) in Nottingham, UK. Methods: This was a retrospective study of patients who presented to the Queen's Medical Centre, Nottingham, with suspected BK during 2015–2019. Relevant data, including the demographic factors, risk factors, clinical outcomes, and potential prognostic factors, were analysed. Results: A total of 283 patients (n = 283 eyes) were included; mean age was 54.4 ± 21.0 years and 50.9% were male. Of 283 cases, 128 (45.2%) cases were culture-positive. Relevant risk factors were identified in 96.5% patients, with ocular surface diseases (47.3%), contact lens wear (35.3%) and systemic immunosuppression (18.4%) being the most common factors. Contact lens wear was most commonly associated with P. aeruginosa whereas Staphylococci spp. were most commonly implicated in non-contact lens-related BK cases (p = 0.017). At presentation, culture-positive cases were associated with older age, worse presenting corrected-distance-visual-acuity (CDVA), use of topical corticosteroids, larger epithelial defect and infiltrate, central location and hypopyon (all p < 0.01), when compared to culture-negative cases. Hospitalisation was required in 57.2% patients, with a mean length of stay of 8.0 ± 8.3 days. Surgical intervention was required in 16.3% patients. Significant complications such as threatened/actual corneal perforation (8.8%), loss of perception of light vision (3.9%), and evisceration/enucleation (1.4%) were noted. Poor visual outcome (final corrected-distance-visual-acuity of <0.6 logMAR) and delayed corneal healing (>30 days from initial presentation) were significantly affected by age >50 years, infiltrate size >3 mm, and reduced presenting vision (all p < 0.05). Conclusion: BK represents a significant ocular morbidity in the UK, with ocular surface diseases, contact lens wear, and systemic immunosuppression being the main risk factors. Older age, large infiltrate, and poor presenting vision were predictive of poor visual outcome and delayed corneal healing, highlighting the importance of prevention and early intervention for BK.